Greed or good deeds: An examination of the relation between corporate social responsibility and the financial performance of U.S. commercial banks around the financial crisis - Cornett, Marcia Millon; Erhemjamts, Otgontsetseg; Tehranian, Hassan (Journal of Banking & Finance, 2016)
We examine the relation between banks’ corporate social responsibility (CSR) and financial performance in a context of the recent financial crisis. We find that banks, in general, appear to be rewarded for being socially responsible as financial performance is positively and significantly related to CSR scores. We find that the biggest banks pursue socially responsible activities to a significantly greater extent than smaller banks. Further, the largest banks see a steep increase in CSR strengths and a steep drop in CSR concerns after 2009.